Primary choroidal melanoma followed by two metachronous ipsilateral ocular metastases - P. T. Finger; C. T. Yin; A. C. Pavlick; N. Farhat (Российский офтальмологический журнал)
Purpose. To describe two ipsilateral, metachronous, ocular choroidal melanoma metastases.Material and methods. A 64-year-old choroidal melanoma patient was initially treated with palladium-103 ophthalmic plaque brachytherapy which induced local control of the primary cancer. Seven years later, ophthalmic findings of a second, ipsilateral, discrete choroidal melanoma prompted restaging which revealed new hepatic and nodal metastases. Systemic immunotherapy (ipilimumab 3 mg/kg with nivolumab 1 mg/kg IV every 3 weeks 4 doses) resulted in intraocular tumor regression and was followed by maintenance nivolumab 480 mg IV every 4 weeks with follow-up ophthalmic examinations.Results. Three years after initiation of systemic immunotherapy, the patient was found to have a second ipsilateral local recurrence of choroidal melanoma. It presented with retinal detachment, uveitis, and optic neuritis. Then, due to its anterior uveal location, extrascleral tumor extension was amenable to a diagnostic biopsy. Overall, 3 years after onset of metastatic uveal melanoma and 2 months after her second ocular metastasis, the patient died. This was 10 years after the initial diagnosis of choroidal melanoma.Conclusions. Metastatic choroidal melanoma can present twice in the same eye as the primary tumor. Ophthalmic and systemic examinations allowed for immunotherapy to affect initial systemic regression, vision sparing, and globe salvage.